LA SIGNIFICACIÓN SOCIAL DE LA FORMACIÓN COMUNICATIVA CIENTÍFICA ESCRITA DE LOS ESTUDIANTES UNIVERSITARIOS - Dugareva, Elena A.; Sánchez, Nereyda Pérez (Universidad & ciencia, 2017)
The work addresses from the focus on Science Technology and Society (STS) the results achieved in the research, led to the formation of written scientific communication college students. The study conducted at the University of Ciego de Avila found the shortcomings of the students in the written transmission of scientific knowledge, limiting their preparation for future roles as creators, communicators and disseminators of scientific and technological society. Teaching strategy is proposed, which based on a model of the dynamics of the formation contextualized scientific written communication to solve the problem and performed partial application. Training written scientific communication achieved by linking the contents of each subject with the task of transmitting them in writing and thus appropriate standards of scientific writing and communication. The implementation of the strategy yielded satisfactory results, contributes to the development of communicative competence to written transmission of scientific knowledge, and improves communication habits of undergraduate students.